Wnt/β-catenin signaling pathway role in the endometriosis pathogenesis - E. V. Virivskaya; I. V. Ignatko; I. A. Snimshchikova; K. R. Bakhtiyarov; A. S. Zueva; T. D. Kapyrina (Акушерство, гинекология и репродукция, 2020)
Endometriosis is a chronic estrogen-dependent disease characterized by the ectopic growth of endometrium-like tissue outside the uterus. In recent years, increasing attention has been paid to the role of the Wnt/β-catenin signaling pathway in endometriosis pathogenesis, wherein it regulates cell proliferation, migration, invasion, and fibrosis. Hyperactivation of the Wnt/β-catenin cascade promotes disease progression, chronic inflammation, and adhesion formation. MicroRNAs modulating this signaling pathway are of particular interest, offering potential for endometriosis diagnostics and targeted therapy. Further research may lead to new treatment approaches and improved quality of patients’ life.